Supramolecular binding and separation of hydrocarbons within a functionalised porous metal-organic framework - Yang, Sihai; Ramirez-Cuesta, Anibal J.; Newby, Ruth; Garcia-Sakai, Victoria; Manual, Pascal; Callear, Samantha K.; Campbell, Stuart I.; Tang, Chui C.; Schröder, Martin (Nature, 2015)
Supramolecular interactions are fundamental to host-guest binding in chemical and biological processes. Direct visualisation of such supramolecular interactions within host-guest systems is extremely challenging but crucial for the understanding of their function. We report a comprehensive study combining neutron scattering with synchrotron X-ray and neutron diffraction, coupled with computational modelling, to define the detailed binding at a molecular level of acetylene, ethylene and ethane within the porous host NOTT-300. This study reveals the simultaneous and cooperative hydrogen-bonding, π···π stacking interactions and inter-molecular dipole interactions in the binding of acetylene and ethylene to give up to twelve individual weak supramolecular interactions aligned within the host to form an optimal geometry for intelligent, selective binding of hydrocarbons. We also report, for the first time, the cooperative binding of a mixture of acetylene and ethylene within the porous host together with the corresponding breakthrough experiment and analysis of mixed gas adsorption isotherms.